Categorization of atomic mixing patterns in bimetallic nanoparticles by the energy competition - Yun, Kayoung; Nam, Ho-Seok; Kim, Seungchul (ROYAL SOC CHEMISTRY, 2020)
The superior properties of bimetallic nanoparticles are strongly related to their morphology. A better understanding of the morphological details would be the first step to design bimetallic nanoparticles for target applications. In this study, we discussed three possible categories of the atomic mixing patterns of bimetallic nanoparticles using the concept of competition between bond energy and surface energy. The categorization was confirmed with the thermodynamically stable structures of AgPt, AuPt, CuPt, PdPt, AgPd, AuPd, and CuPd obtained using Monte Carlo simulations. This work also proposed the phase diagrams of AuPt, CuPt, and PdPt nanoparticles, which displayed the details of atomic arrangements depending on the changes in size and atomic composition. The population in low-coordination sites and temperature effects were also intensively studied. The comprehensive understanding of these factors would facilitate the rational design and wide applications of bimetallic nanoparticles.
Keywords: CORE-SHELL; PT-PD; OXYGEN REDUCTION; SEGREGATION; CATALYSTS; SHAPE; NI